The Role of Learning Media in the Implementation of Citizenship Education - Br Tarigan, Eyu Nike Puri (International Journal of Students Education, 2025)
The role of learning media in the learning and teaching process is an integral part of the world of education. The use of learning media will really help the effectiveness of the learning process and delivery of messages and lesson content. The aim of this research is to determine the role of learning media in strengthening civic education learning in elementary schools. This research uses the Literature Review method, a method used by literature reviews. With this type of research, sources are collected from books, magazines, journals, articles, and documents that are appropriate for the study to be analyzed. The results of the research show that the role of learning media in strengthening civic education learning in elementary schools is to clarify presentation of messages so that they are not too verbal, dissemination of information widely, evenly, quickly, uniformly and with integrity, so that can be delivered according to what is intended or desired, Technology can present it logically, scientifically and systematically and is able to complement, support and clarify students concepts, principles or proportions of subject matter, using appropriate media and varied learning, it can overcome messages’ passive attitudes.